Pengamanan File Teks Dengan Algoritma Enkripsi Pohlig-Hellman Dan Steganografi Ezstego Pada File Audio - Herwansyah, Herwansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In cryptography, the encryption process is carried out by changing the data into another form of data that cannot be understood and its meaning can be understood. However, with other forms of data, this can raise suspicion, so after the data is encrypted, it is necessary to hide the data into an object without changing the object's shape using steganography techniques. The process of double securing text files is done by using cryptographic techniques using the Pohlig-Hellman algorithm, then the encryption results in the form of ciphertext are inserted back into the audio object using the Ezstego algorithm. From the analysis, the ciphertext characters that have been encrypted using the Pohlig-Hellman algorithm can be accurately inserted into the audio object without changing the audio form using the Ezstego algorithm.